Wątki egipskie w greckich opowieściach mitycznych - Taterka, Filip (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2025)
The paper discusses the reception of Egyptian motifs in Greek mythography based on three case studies: Herodotus’ Histories, Diodorus Siculus’ Library of History and Plato’s Phaedrus. It is argued that all of these works contain elements that find their parallels in either Late Egyptian or Demotic texts. The content of these was made accessible to the Greek authors either through written translations or oral conversations with Egyptian priests. As a result, it is argued that the idea that naming Egyptian priests as a source of knowledge by the classical authors should not be automatically interpreted as a mere topos, since this might actually reflect historical reality, at least in some instances.